Selective Sensing of Tyrosine Phosphorylation in Peptides Using Terbium(III) Complexes - Jun Sumaoka; Hiroki Akiba; Makoto Komiyama (International Journal of Analytical Chemistry)
Phosphorylation of tyrosine residues in proteins, as well as their dephosphorylation, is closely related to various diseases. However, this phosphorylation is usually accompanied by more abundant phosphorylation of serine and threonine residues in the proteins and covers only 0.05% of the total phosphorylation. Accordingly, highly selective detection of phosphorylated tyrosine in proteins is an urgent subject. In this review, recent developments in this field are described. Monomeric and binuclear TbIII complexes, which emit notable luminescence only in the presence of phosphotyrosine (pTyr), have been developed. There, the benzene ring of pTyr functions as an antenna and transfers its photoexcitation energy to the TbIII ion as the emission center. Even in the coexistence of phosphoserine (pSer) and phosphothreonine (pThr), pTyr can be efficintly detected with high selectivity. Simply by adding these TbIII complexes to the solutions, phosphorylation of tyrosine in peptides by protein tyrosine kinases and dephosphorylation by protein tyrosine phosphatases can be successfully visualized in a real-time fashion. Furthermore, the activities of various inhibitors on these enzymes are quantitatively evaluated, indicating a strong potential of the method for efficient screening of eminent inhibitors from a number of candidates.